Acute effects of different external compression with blood flow restriction on force-velocity profile during squat and bench press exercises - Serrano-Ramon, Josep; Cortell-Tormo, Juan; Bautista, Iker; García Jaén, Miguel; Chulvi-Medrano, Iván (Biology of Sport, 2023)
The aim was to compare the acute effects of bench press (BP) and squat (SQ) exercises with blood flow restriction (BFR) (40%, 60%, 80% and 100% of the complete arterial occlusion pressure (AOP)) and without BFR (CON) on the mean propulsive (VelMED) and maximum (VelMAX) bar velocity. Fourteen healthy, physically active males (age, 23.6±4.1 years; height, 1.85±0.11 m; body weight 85.4±4.1 kg) took part in the study. There was one set for each testing condition (CON, 40%, 60%, 80% and 100%) with 6 repetitions for BP and 6 repetitions for SQ, at 60% of 1RM, and 3 minutes of recovery between sets. The results showed statistically significant differences of the sets with 80% BFR vs. CON (mean difference [MD] = 0.035 m·s-1, p < 0.05, ES = 0.52 [1.02–0.03]) and 100% BFR sets vs. CON (MD = 0.074, p < 0.001, ES = 1.08 [1.79–0.38]) for BP. In the SQ exercise, statistically significant differences were found between 100% BFR vs. CON (DM = 0.031 m·s-1, p < 0.05), vs. 100% BFR 40% (MD = 0.04 m·s-1, p < 0.05). Trend analysis showed a statistically significant linear trend (F[1,9] = 34.9, p < 0.001, F[1,13] = 27.32, p < 0.001) for the VelMED in relation to the different levels of BFR. In conclusion, our results showed that BFR levels above ~80% AOP (BP) and ~100% AOP (SQ) produce a VelMED improvement at 60% 1RM.